Diagnostic error in detection of fractured and migrated totally implantable venous access device fragments and experience with percutaneous retrieval: A report of 27 cases. Issue 2 (March 2022) - Matton, Tom; Coolen, Johan; Vanhaecht, Kris; Boecxstaens, Veerle; Fourneau, Inge; Maleux, Geert
Purpose: To assess diagnostic efficacy/error to identify broken or dislocated totally implantable venous access device (TIVAD) fragments on radiological studies and to analyze interventional outcome of percutaneous retrieval. Materials and methods: Retrospective, single-center analysis of 27 patients, referred for percutaneous retrieval of embolized TIVAD fragments between 2000 and 2018. Demographic data, underlying disease, diagnostic studies, diagnostic error, interval between implantation and diagnosis of TIVAD-dysfunction, interval between diagnosis and retrieval, anatomical location of the embolized fragments, and technical aspects of retrieval procedure were identified from the patients' electronic medical records. Results: Overall, diagnostic error was found in six patients (22%) with an average delay of 53 days. Ten fractures were caused during surgical removal, eleven fractures by pinching between first rib and clavicle and six cases by spontaneous disconnection between reservoir and catheter. Success rate of retrieval was 96% and the complication rate 0%. Conclusion: Fractured or retained TIVAD fragments were initially overlooked on radiological studies in more than 20% of patients. Percutaneous retrieval of broken and dislocated TIVAD fragments is very safe and highly successful.